Caribbean cooperation and integration : the OECS experience (OECS Central Secretariat CastriesLC, 1987)
Reviews the background to the development of the OECS. Discusses its experiences in the areas of economic and functional cooperation and shows why some of that experience suggests the need for a closer relationship among the OECS countries.
IDS